TEACHERS' TRAINING AND INCLUSIVE METACOGNITIVE TOOLS - Vinci, Viviana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
A Research&Training project has been set up involving people attending courses for teaching qualification; the aim was to develop metacognitive tools to create inclusive reflection methodologies aimed at enhancing mental skills dealing with inclusive education. The theoretical framework combines the studies in professional Education and Teachers' Thinking with reflection-based and metacognitive training paradigms. By means of workshops, a reflecive-oriented metacognitive tool for inclusive training has been created; four individual writing activities were carried out, including professional writing, maps and case studies, together with a group project. The results showed the need to develop new educational devices and a shared language of teachers' professional knowledge that can be useful to adapt any context in the inclusive perspective of the so-called Education for all.